Spatial and temporal expression profiles of urocortin 3 mRNA in the brain of the chicken (Gallus gallus). Issue 11 (8th May 2017) - Grommen, Sylvia V. H.; Scott, Melissa K.; Darras, Veerle M.; De Groef, Bert
Abstract: Urocortin 3 (UCN3) is a neuropeptide believed to regulate stress‐coping responses by binding to type 2 corticotropin‐releasing hormone receptors. Here, we report the cloning and brain distribution of UCN3 mRNA in a sauropsid—the chicken, Gallus gallus . Mature chicken UCN3 is predicted to be a 40‐amino acid peptide showing high sequence similarity to human (93%), mouse (93%), and Xenopus (88%) UCN3. During the last third of embryonic development, UCN3 mRNA levels changed differentially in the various brain parts. In all brain parts, UCN3 mRNA levels tended to increase toward hatching, except for caudal brainstem, where a gradual decrease was observed during the last week of embryonic development. In cerebellum, a rapid increase in gene expression occurred between embryonic days 17 and 19. Using in situ hybridization, UCN3 mRNA was found to be expressed predominantly in the hypothalamus, pons, and medulla of posthatch chick brains, but not in some areas that are among the main expression sites in rodents, such as the brain areas where in mammals the median preoptic nucleus and the medial amygdala are located. This suggests that the roles of UCN3 in chicken, and perhaps sauropsids in general, are not all identical to those in rodents. Abstract : The distribution of urocortin 3 mRNA in chicken brain is different to that in rodents, including in the hypothalamus and amygdala. This indicates different roles in birds. Spatial and temporal expression patterns suggest a role in motor control of the digestive system and maturation of certain neuronal circuits.